Physiologic and pharmacologic properties of normal and dystrophic muscle in the domestic fowl (Gallus domesticus) - Howlett, Susan E., 1957- (1985)
Thesis (Ph.D.) -- Memorial University of Newfoundland, 1985. Medicine Bibliography : leaves 208-232.